Condition-based maintenance policy for linear consecutive-k-out-of-n: F system. Issue 4 (21st April 2017) - Endharta, Alfonsus Julanto; Yun, Won Young
ABSTRACT: In the article, a condition-based maintenance policy is proposed for a linear consecutive- k -out-of- n : F system. The failure times of components are assumed to be independent and identically distributed. It is assumed that the component states in the system can be known at any time and the system failure can be detected immediately. The preventive maintenance action is based on the number of working components in minimal cut sets of the system. If there is at least one minimal cut set consisting of only one working component, the system is maintained preventively after a certain time interval. The proposed policy is compared with corrective maintenance and age-based maintenance policies. As an extended case, it is assumed that the component states can only be known by inspection, but the system failure can be detected immediately. In this case, the system is inspected periodically and is also maintained preventively based on the system state at inspection. Numerical examples are studied to evaluate the performance of the proposed policy and investigate the effects of cost parameters on the expected cost rate.